Transparency in Spanish Government in Times of Covid-19. (30th November 2022) - Cifuentes-Faura, Javier
Abstract: Transparency is fundamental for the development of good governance, and even more so in times of crisis. The current crisis caused by the coronavirus has raised questions worldwide as to whether the government is acting transparently. In the case of Spain, the state of alarm decreed has suspended the terms and interrupted the deadlines for processing the procedures of public sector entities, including those affecting the Law on Transparency. This paper analyses how this suspension is affecting the actions carried out in Spain. It shows those practices that we consider to violate citizens' right to public information, and which are therefore not transparent. In Spain, there has been a setback in terms of access to public information and transparency, which has not only been visible in the management of COVID-19 data, but has also affected other areas such as public procurement.